Stigma in Welfare Programs - Pablo Celhay; Bruce D. Meyer; Nikolas Mittag (Institute of Labor Economics (IZA), 2022)
Stigma of welfare participation is important for policy and survey design, because it deters program take-up and increases misreporting. Stigma is also relevant to the literature on social image concerns, yet empirical evidence is scant because stigma is difficult to empirically identify. We use a novel approach to studying stigma by examining the relationship between program participation in a recipient's local network and underreporting program participation in surveys. We find a robust negative relationship and rule out explanations other than stigma. Stigma decreases when more peers engage in the stigmatized behavior and when such actions are less observable.
Keywords: D19; D85; D91; I38; Z13; 330; welfare stigma; program participation; social networks; social image; peer effects